2017
DOI: 10.1007/s10461-017-1914-3
|View full text |Cite
|
Sign up to set email alerts
|

Foreign-Born Individuals with HIV in King County, WA: A Glimpse of the Future of HIV?

Abstract: To better understand country of birth-related shifts in the demography of people newly diagnosed with HIV infection, we compared demographic and clinical characteristics of foreign-born and U.S.-born residents of King County, WA diagnosed with HIV from 2006 to 2015. The proportion of cases that were foreign-born increased from 23 to 34% during this time. Most foreign-born cases were born in Africa (34%), Latin America (32%), Asia (22%), or Europe (7%). Latin Americans and Asians were similar to U.S.-born indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…We did not ascertain detailed HIV risk factor information from study participants, making it difficult to assess the underlying HIV risk of participants. However, specific behavioral risk factors that predict HIV acquisition are not well understood for African-born immigrants, who come from a generalized epidemic setting and often report low numbers of partners [1,3,38]. Last, African-born communities in high-income countries exhibit substantial heterogeneity in country of origin, access to health services, and culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not ascertain detailed HIV risk factor information from study participants, making it difficult to assess the underlying HIV risk of participants. However, specific behavioral risk factors that predict HIV acquisition are not well understood for African-born immigrants, who come from a generalized epidemic setting and often report low numbers of partners [1,3,38]. Last, African-born communities in high-income countries exhibit substantial heterogeneity in country of origin, access to health services, and culture.…”
Section: Discussionmentioning
confidence: 99%
“…Foreign-born individuals comprise an estimated 16% of people newly diagnosed with HIV in the U.S. [1] In King County, Washington, African-born individuals account for 2% of the population yet 10% of new HIV diagnoses [2,3]. Migrant populations face individual, social, and structural barriers to HIV testing in the U.S, including stigma, language barriers, limited financial resources, and insufficient provider cultural competency [4].…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of migrants to the HIV epidemic in Western Europe has long been recognized, 1 and recently, some local health jurisdictions in the U.S. have reported that the proportion of new HIV diagnoses occurring among foreign-born people is increasing over time. 2,3 Understanding the epidemiology of HIV in this population, including when and where people acquired HIV, is instrumental in developing effective strategies to prevent HIV among international migrants.…”
Section: To the Editorsmentioning
confidence: 99%
“…Most originate from countries in South and East Asia, Latin America, sub‐Saharan Africa and the Caribbean and may therefore be considerably different in terms of socio‐cultural characteristics and health status compared with persons born in the US [2]. Studies in the US and Western Europe have suggested that the rate of HIV diagnosis may be higher among foreign‐born persons when compared with native‐born populations [3‐7]. For instance, adult HIV incidence rate in the Caribbean is second only to that in sub‐Saharan Africa [8].…”
Section: Introductionmentioning
confidence: 99%
“…Foreign‐born populations, especially women are generally disadvantaged in terms of accessing health care due to a complex set of social and structural factors [5,9‐11], all of which exert powerful negative influences on short‐ and long‐term health outcomes[6,9,12‐17]. Studies suggest that foreign‐born women are more susceptible to the less desirable outcomes of HIV due to low socioeconomic and educational status, language barriers, poor access to health providers, lack of transportation, and lack of documented legal status, among others, and may be negatively impacted in accessing or utilizing services because of similar factors [17,18].…”
Section: Introductionmentioning
confidence: 99%